2002
DOI: 10.5713/ajas.2002.1433
|View full text |Cite
|
Sign up to set email alerts
|

Leucaena Seeds as Protein Supplement in the Rations of Growing Sheep

Abstract: The study was carried out to evaluate leucaena seeds as a protein replacement of mustard seed cake (MSC) in the concentrate mixture of growing lambs. Fifteen growing male lambs (Local×Corridale) with an average body weight of 16.3 kg were allocated into three dietary treatments (T1, T2, and T3) with five animals in each group. Animals were offered dry mixed grass, berseem hay and concentrate mixture to meet their nutrient requirements. In concentrate mixture of T1, (Control) MSC was used as protein source, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Santana et al [ 62 ] found better intake and nutrient digestibility in lambs when fed with silage mixture with Leucaena and better N retention when fed alone. In lambs, the replacement of mustard seeds with Leucaena seeds, as a protein source up to 50%, did not produce adverse effects on the ingestion of the dry matter, the use of nutrients, the nitrogen balance, and the growth performance [ 63 ].…”
Section: Swot Analysismentioning
confidence: 99%
“…Santana et al [ 62 ] found better intake and nutrient digestibility in lambs when fed with silage mixture with Leucaena and better N retention when fed alone. In lambs, the replacement of mustard seeds with Leucaena seeds, as a protein source up to 50%, did not produce adverse effects on the ingestion of the dry matter, the use of nutrients, the nitrogen balance, and the growth performance [ 63 ].…”
Section: Swot Analysismentioning
confidence: 99%